The validity and the reliability of Turkish Version of Children's Sleep Habits Questionnaire - (:unkn) unknown (CUMHURIYET UNIV TIP FAK PSIKIYATRI ANABILIM DALI, 2010)
Objective: The objective of this study was to examine the validity and the reliability of Turkish version of Children's Sleep Habits Questionnaire (CSHQ)-Abbreviated Form. Methods: The sample consisted of 1749 1(st), 2(nd), 3(rd), and 4(th) grade elementary schoolchildren. The parents were asked to complete the CSHQ, sociodemographic form, and a question list assessing the behavioral and emotional problems of children. Internal consistency, test-retest reliability, and construct validity of the CSHQ were investigated. Results: Cronbach's alpha coefficient was determined as 0.78. The test retest correlation coefficient was 0.81 (p<0.001). As a result of factor analysis 11 factors were determined. Additional analysis regarding the construct validity indicated that the total sleep scores did not differ by age and gender (p>0.05), yet the scores tended to increase with decreasing socioeconomic status (p<0.001). There were statistically significant relationships between all behavioral and emotional parameters and the presence of sleep problems. Conclusion: These results suggest that Children's Sleep Habits Questionnaire, which is a parent proxy-report, is a valid and reliable instrument for assessing sleep habits and screening possible sleep problems of Turkish children. (Anatolian Journal of Psychiatry 2010; 11:151-160)
Keywords: sleep problems; child; questionnaire; validity; reliability; SCHOOL-AGED CHILDREN; MAJOR DEPRESSION; SYMPTOMS; DISORDERS; HYPERACTIVITY; ADOLESCENTS; INATTENTION; PREDICTORS; QUALITY; ANXIETY